Social Media Management of the MIK SEMAR Facebook Group as an Information Media for the People of Semarang City - Ayang Fitrianti Ayang; Ahmad Taufikurrohman (Universitas Muhammadiyah Sidoarjo, 2023)
Needs for information is currently increasing with the high level of use of social networking sites in society. Facebook is a social networking site with various features, one of which is the MIK SEMAR Facebook group which allows people in the city of Semarang to easily access various information such as infrastructure, transportation, buying and selling of products, local events and issues related to Semarang. This research method is descriptive qualitative, data collection techniques used are interviews, observation and documentation. The theory used in this study is The Circular Model of SOME. In the results of this study it can be concluded that the steps to share information on the MIK SEMAR Facebook group facilitate the formation of public understanding. In terms of optimization, MIK SEMAR's Facebook team has done everything to listen and understand what the public is talking about. The management aspect carried out by the MIK SEMAR Facebook group is quite good. Aspects of engaging Facebook Group MIK SEMAR understands the importance of reaching the audience and providing a fast response to reach the target audience.